Exploring the Prevalence of Burnout in Medical Residents: Socio-Demographic and Job Characteristics as Predictors in Iran - Shakiba, Shima; Sharifi, Ahmad; Hashemi, Farnaz; Mazinani, Zahra; Sorouri, Majid; Safarpour, Ali Reza; Saranjam, Elham; Soltani, Fereshteh; Merat, Shahin; Ghanbari, Reza; Poustchi, Hossein (Universitas Airlangga, 2025)
Introduction: Burnout is a psychological syndrome that develops due to chronic stressors in a person's professional life, resulting in emotional exhaustion and detachment. The objective of this study was to determine the prevalence of burnout among medical residents, considering socio-demographic variables and job characteristics, and to predict burnout in this group. Medical residents often face specific pressures such as long working hours, sleep deprivation, high patient loads, and emotional demands from patient care, which contribute to their overall stress levels. Methods: A cross-sectional study was conducted in the academic year 2019-2020, involving 164 residents from two general hospitals who completed the Persian versions of the Job Content Questionnaire (JCQ) and Maslach Burnout Inventory (MBI-HSS). Results: A significant proportion of residents reported burnout symptoms, with 73.7% experiencing moderate to high levels of emotional exhaustion and 64.4% indicating moderate to high levels of depersonalization. Additionally, 90.1% of residents reported low perceived professional efficacy. Among the subscales of MBI-HSS, reduced professional efficacy was found to be the highest. Psychological demands and limited decision latitude were significant predictors of burnout, particularly in relation to emotional exhaustion and depersonalization. Conversely, support from family and co-workers, as well as higher levels of experience, were associated with lower depersonalization and improved professional efficacy. Conclusion: Overall, medical residents in Iran face significantly high levels of burnout, which are influenced by specific personal and job characteristics. Consequently, preventive and therapeutic interventions are necessary to address this pressing issues.